2021
DOI: 10.1111/jonm.13426
|View full text |Cite
|
Sign up to set email alerts
|

Manager's influence on the registered nurse and nursing assistant relational quality and patient safety culture

Abstract: Aims The purpose of this study is to describe the perceptions of relational quality of the registered nurse and nursing assistant and examine how their view of the manager's influence impacts overall patient safety culture of a unit. Background The primary delivery of nursing care within acute care systems uses teams of registered nurses and nursing assistants. Methods A cross‐sectional secondary analysis of data collected in the spring of 2018 using the Agency for Healthcare and Quality Hospital Survey of Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Thirty-five studies from databases were included in the scoping review, and one study published from 2011 to 2021 were manually identified from the reference lists. Ultimately, we identified 36 eligible studies38–73 for our scoping review (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-five studies from databases were included in the scoping review, and one study published from 2011 to 2021 were manually identified from the reference lists. Ultimately, we identified 36 eligible studies38–73 for our scoping review (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…38 2. A seven-item leader-member exchange relational quality questionnaire from Campbell et al 39 and developed by Graen and Uhl-Bien. 76 3.…”
Section: Appraisal Toolsmentioning
confidence: 99%
“…(1) HCA & RNs' intention questionnaire; 38 (2) LMX-7 relational quality questionnaire from Campbell et al 39 and developed by Graen et al; 76 (3) NA working questionnaire 47 ; (4) the Nursing Culture Assessment Tool (NCAT); 49 (5) the Structured Multidisciplinary Evaluation Tool (SMET) from Haraldsson et al 48 and developed by the author in 2016; 77 (6) Self-Efficacy for Preventing Falls -Assistants (SEPFA); 42 (7) the Work Ability Index from Monteiro et al 54 and produced by Ilmarinen. 78 Three of seven papers developed original scales and tested reliability and validity.…”
Section: Appraisal Toolsmentioning
confidence: 99%
“…Adequate staffing, managerial support for nurses and good nurse–physician relations contribute to a professional nurse work environment (IOM, 2004 ). Hospital manager behaviours that promote patient safety and transformational leadership styles influence and predict nurse‐perceived patient safety (Anderson et al, 2019 ; Campbell et al, 2021 ; Ferreira et al, 2022 ; Lee & Dahinten, 2020 ; Weaver et al, 2017 ). Transformational leadership had a significant indirect effect on adverse patient outcomes through structural empowerment (Boamah et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%